2004
DOI: 10.1023/b:apih.0000042743.11286.bc
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Teaching Practice: Implications for Behavioral Health

Abstract: Educational practices and strategies have changed very little over the years, and even emerging advances in technology have become the prisoners of traditional academic norms. Thus, while there is increasing emphasis on evaluating and aligning caregiving processes with the strongest evidence of effectiveness, there is little demonstration or role-modeling of this same expectation in either the formal or continuing educational processes of behavioral healthcare providers. This "disconnect" is a significant prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 59 publications
1
69
0
1
Order By: Relevance
“…In regard to knowledge gains, however, the reported success may very well not translate into changes in practice. In general the benefits of workshops in producing practice change have been inconsistent and modest at best, although presentations such as ours that are interactive in design (e.g., involve roleplay, discussion, and experiential exercises) have had better success in producing practice change (Grol and Grimshaw 2003;Stuart et al 2004). Encouragingly Ranz and Mancini (2008) reported that there is an association between knowledge of recovery concepts and recovery-oriented practices.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to knowledge gains, however, the reported success may very well not translate into changes in practice. In general the benefits of workshops in producing practice change have been inconsistent and modest at best, although presentations such as ours that are interactive in design (e.g., involve roleplay, discussion, and experiential exercises) have had better success in producing practice change (Grol and Grimshaw 2003;Stuart et al 2004). Encouragingly Ranz and Mancini (2008) reported that there is an association between knowledge of recovery concepts and recovery-oriented practices.…”
Section: Discussionmentioning
confidence: 99%
“…of knowledge (Stuart, Tondora, & Hoge, 2004), the competencies we have identified fall into the skills domain. Employment specialists excelled in being prepared yet flexible when going out to job develop.…”
Section: Competencies Of Employment Specialists For Effective Job Devmentioning
confidence: 97%
“…The strategies known as ''demonstration'' and ''return demonstration'' may be particularly useful for the acquisition of job development skills. In this process, a teacher models a desired skill or behavior and the learner subsequently demonstrates the behavior to the teacher and receives individualized feedback on his or her performance (Stuart et al, 2004). Initial didactic trainings and follow-up booster trainings could be offered by consultants to model job development strategies shown to be effective.…”
Section: Competencies Of Employment Specialists For Effective Job Devmentioning
confidence: 99%
“…Third, it was self-evident that the targets of Project GREAT'S efforts were adults and thus the principles and science of teaching adult learners needed to be incorporated. Based on representative educational theory and research of adult learners (Stuart, Tondora, & Hoge, 2004;Zisook et al, 2005), the following instructional strategies were adopted by Project GREAT:…”
Section: Step 3: Analysis Of Learner Characteristicsmentioning
confidence: 99%